Status of thyroid hormones and its relation with eGFR in non-hemodialyzed advanced chronic kidney disease – A hospital-based cross-sectional study - Ranajit Bari; Subhajit Paul; Kuntolika Mani; Partha Sarathi Karmakar (Asian Journal of Medical Sciences, 2023)
Background: Patients with chronic kidney disease (CKD) and significantly low estimated glomerular filtration rate (eGFR) or end-stage kidney disease have been linked to thyroid dysfunction. Renal function is also negatively impacted by thyroid disease. Aims and Objectives: This study was conducted to find out magnitude of thyroid disorder in advanced CKD and to correlate eGFR with thyroid function status. Materials and Methods: A hospital-based study was conducted among CKD patients to assess the thyroid disorders and its associated factors. A thorough clinical history was taken on chief complaints, any additional precipitating factors or co-morbidities (such as diabetes and hypertension), the use of any medications other than those for CKD in the past, any significant surgical procedures, and any episodes of hemodialysis. A morning blood sample was collected for thyroid function (T3, Free T3, T4, Free T4, and thyroid-stimulating hormone [TSH]) and kidney function test. According to KDIGO’s criteria 2017, CKD was identified. Results: The current study included 60 individuals, with a majority of men (56.7%) and a mean (SD) age of 48.8 (8.4) completed years. 28.3% had low T3 syndrome. Hypothyroidism was seen by 15% and 28.3% had subclinical hypothyroidism. There was no identified hyperthyroidism patient. eGFR had positive correlation with free T3 (r=0.46, P=0.0002). It had a low positive (r=0.03, P=0.7) and weakly positive (r=0.14, P=0.2) correlation with total T3 and total T4. Free T4 and TSH both had negative correlations with eGFR (r=−0.17, P=0.1 and r=−0.09, P=0.4, respectively). Conclusion: Patients with CKD had non-specific thyroid impairment, or decreased total T3 alone but no hyperthyroidism at presentation. The progression of CKD stage made it worse. There was significant positive correlation between free T3 and eGFR.